Pre-Announcement Market Behavior: Evidence from Oil Trading Activity and Temporal Dislocation - Husain Alaali, Hasan Mohamed (The American Journal of Interdisciplinary Innovations and Research, 2026)
Financial markets are generally viewed as information-driven systems in which trading activity and price adjustments follow the release of new information. Yet market behavior does not always conform neatly to this sequence. This study investigates a notable event in the oil futures market that occurred in March 2026, where unusually concentrated trading activity and price movements were observed approximately fifteen minutes before an official political announcement concerning Iran. The event raises a fundamental question: can observable market behavior emerge before formal information enters the public domain? Existing explanations would typically point to information asymmetry, insider trading, or informed order flow. While such mechanisms remain relevant, they do not fully capture situations in which substantial market activity develops despite the absence of clearly identifiable public signals. To explore this issue, the study draws on insights from behavioral economics, behavioral finance, market microstructure, and price discovery research [7–11,16,19]. It introduces the concept of Pre-Announcement Behavioral Dislocation (PABD), a framework that focuses on the temporal relationship between expectations, uncertainty, trading behavior, and formal information disclosure. The central argument is that market participants may react to evolving expectations, contextual developments, and perceived signals before information becomes formally confirmed, creating observable market effects ahead of official announcements. Rather than treating such episodes solely as anomalies or evidence of information leakage, the paper examines whether they may reflect a broader behavioral pattern that appears across different contexts. The findings suggest that pre-announcement activity deserves greater attention within financial research because it challenges announcement-centered assumptions about timing and market response. By emphasizing the role of expectation formation and behavioral dynamics under uncertainty, the study contributes to ongoing discussions regarding market efficiency, price formation, and the processes through which markets interpret emerging developments.